Long-term scarring outcomes and safety of patients treated with NovoSorbⓇ Biodegradable Temporizing Matrix (BTM): An observational cohort study - C.H. Lo; M.J.D. Wagstaff; T.M. Barker; L. Damkat-Thomas; S. Salerno; D. Holden; E. Concannon; K. Heath; P. Coghlan; H. Cleland (JPRAS Open, 2023)
Background/Aim: NovoSorbⓇ Biodegradable Temporizing Matrix (BTM) is a relatively novel, biodegradable polyurethane-based dermal regeneration template. The aim of this study was to evaluate the long-term scarring outcomes and safety of BTM in patients who underwent dermal reconstruction involving ≥5% of the total body surface area. Methods: This was a postmarket, multicenter, observational cohort study involving evaluation of long-term outcomes in patients treated with BTM. A total of 55 patients (35 from Royal Adelaide Hospital, South Australia, and 20 from Victoria Adult Burns Service, The Alfred, Victoria) who underwent dermal repair with BTM between 2011 and 2017 were screened for inclusion in this study. All patients had BTM implanted for ≥18 months. Results: Fifteen eligible patients with a mean (SD) age of 49.1 (14.3) years completed study assessments. These patients had a total of 39 areas treated with BTM. Using the Patient and Observer Scar Assessment Scale, scar quality was reported to be good by both observers and patients, with a mean (SD) observer score across all lesions of 3.6 (1.2) and mean (SD) overall opinion of 3.8 (1.2) as well as a mean (SD) patient score of 3.5 (1.2) and overall opinion of 5.0 (2.2). No adverse events or adverse device effects were reported or identified. Conclusion: The long-term scar quality is comparable to published studies. BTM is safe in the long term with no additional risks or adverse consequences being identified.